Rotavirus strain distribution in Ghana pre- and post- rotavirus vaccine introduction. Issue 47 (12th November 2018) - Lartey, Belinda L.; Damanka, Susan; Dennis, Francis Ekow; Enweronu-Laryea, Christabel C.; Addo-Yobo, Emmanuel; Ansong, Daniel; Kwarteng-Owusu, Sandra; Sagoe, Kwamena W.; Mwenda, Jason M.; Diamenu, Stanley K.; Narh, Clement; Binka, Fred; et al.
Abstract: Background: Ghana introduced the monovalent rotavirus vaccine (Rotarix) into its national paediatric vaccination programme in May2012. Vaccine introduction was initiated nationwide and achieved >85% coverage within a few months. Rotavirus strain distribution pre- and post-RV vaccine introduction is reported. Methods: Stool samples were collected from diarrhoeic children <5 years of age hospitalized between 2009 and 2016 at sentinel sites across Ghana and analyzed for the presence of group A rotavirus by enzyme immunoassay. Rotavirus strains were characterized by RT-PCR and sequencing. Results: A total of 1363 rotavirus EIA-positive samples were subjected to molecular characterization. These were made up of 823 (60.4%) and 540 (39.6%) samples from the pre- and post-vaccine periods respectively. Rotavirus VP7 genotypes G1, G2 and G3, and VP4 genotypes P[6] and P[8] constituted more than 65% of circulating G and P types in the pre–vaccine period. The common strains detected were G1P[8] (20%), G3P[6] (9.2%) and G2P[6] (4.9%). During the post-vaccine period, G12, G1 and G10 genotypes, constituted more than 65% of the VP7 genotypes whilst P[6] and P[8] made up more than 75% of the VP4 genotypes. The predominant circulating strains were G12P[8] (26%), G10P[6] (10%) G3P[6] (8.1%) and G1P[8] (8.0%). We also observed the emergence of the unusual rotavirus strain G9P[4] during this period. Conclusion: Rotavirus G1P[8], the major strain in circulation during the pre-vaccination era, was replaced by G12P[8] as the most predominant strain after vaccine introduction. This strain replacement could be temporary and unrelated to vaccine introduction since an increase in G12 was observed in countries yet to introduce the rotavirus vaccine in West Africa. A continuous surveillance programme in the post-vaccine era is necessary for the monitoring of circulating rotavirus strains and the detection of unusual/emerging genotypes.